ÙØ¸ÙÙÙØ© Ø§ÙÙØºÙØ© ÙÙ Ø§ÙØ¹Ù ÙÙÙØ© Ø§ÙÙ ÙÙØ§ØµÙÙÙØ© - Ridha, Rasyid (Institut Agama Islam Negeri (IAIN) Palu, 2007)
This article deals with the functions of a language in a communication act. People communicate using a language to convey their points to others. A communication act contains 1) a locutionary act; 2) an illocutionary act; and 3) a perlocutionary. Therefore, to reflect the above three communication acts, people have to know, first, the communicative functions of a language in order to know how to communicate with others effectively, both in articulating voices, words, and sentences. Besides, a message they convey can be quickly deconstructed and interpreted by listeners.Kata Kunci:Â Â Â Â Ù ÙØªÙØ§Ø Ø§ÙÙÙÙÙ , Fungsi Komunikatif Bahasa Â